OUTBURST CYCLICITY OF DWARF NOVA VZ AQUARII - Shakun, L. I. (Одеські астрономічні публікації, 2017)
New linear elements for outbursts of VZ Aqr from 1904 to 1987 were obtained with P0 = 50.4053d. Two states of outburst activity are distinguished with cycle lengths 47.128d and 55.041d, replacing each other during Π = 13.2yr and accompanied by a maximum brightness changes. Instability parameters of VZ Aqr – lg P, lg P/Po, lg Π and lg N0 agree well with a dependence of these parameters on lg P0 derived by the author for other dwarf Novae.